Sparbössor och silverskedar: Dopgåvor som materialiserade känslor - Hagström, Charlotte (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
Gift-giving is part of the ceremonial behaviour in many celebrations associated with rites of passage. In this article I discuss the gifts children receive at christening parties. Even though some parents emphasize that they do not want "typical" christening presents, like pewter savings-boxes or silver photography frames, they often find that the guests nevertheless have brought such gifts. An explanation for this is that the "typical" christening gifts may be perceived as necessary: without them the christening doesn’t feel "right". Another common gift is a coffee silver spoon, which is to be followed by others of the same type at future birthdays. These are often godparents’ gifts and can thus be considered as a materialised manifestation of a relation that is meant to last. Although the christening of a child is a religious act it is also an event which serves to create a sense of family community and belonging and to build relations. The gifts the child receives has, like all gifts, a value not only for the gift-receiver but also for the gift-giver.